Design and performance of Fuzzy Logic Speed controller for DC Motor / Kamarul Azwan Mohd Zawawi - Mohd Zawawi, Kamarul Azwan (2003)
This thesis presents the research study and design of a Fuzzy Logic Controller (FLC) to be implemented in the experiment of DC Motor speed controller. Separately excited DC motor with fuzzy controller is simulated. The linear and optimization process of fuzzy logic controller (FLC) is supported by tuning parameter from Proportional Integrative Derivative (PID) controller.